Efficient Image Super-Resolution with Multi-Branch Mixer Transformer - Long Zhang; Yi Wan (Image Analysis and Stereology)
Deep learning methods have demonstrated significant advancements in single image super-resolution (SISR), with Transformer-based models frequently outperforming CNN-based counterparts in performance. However, due to the self-attention mechanism in Transformers, achieving lightweight models remains challenging compared to CNN-based approaches. In this paper, we propose a lightweight Transformer model termed Multi-Branch Mixer Transformer (MBMT) for SR. The design of MBMT is motivated by two main considerations: while self-attention excels at capturing long-range dependencies in features, it struggles with extracting local features. Secondly, the quadratic complexity of self-attention forms a significant challenge in building lightweight models. To address these problems, we propose a Multi-Branch Token Mixer (MBTM) to extract richer global and local information. Specifically, MBTM consists of three parts: shifted window attention, depthwise convolution, and active token mixer. This multi-branch structure handles both long-range dependencies and local features simultaneously, enabling us to achieve excellent SR performance with just a few stacked modules. Experimental results demonstrate that MBTM achieves competitive performance while maintaining model efficiency compared to SOTA methods.